2020
DOI: 10.7554/elife.53476
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of a quality control protease in E. coli reshapes the in vivo mutational landscape of a model enzyme

Abstract: Protein mutational landscapes are shaped by the cellular environment, but key factors and their quantitative effects are often unknown. Here we show that Lon, a quality control protease naturally absent in common E. coli expression strains, drastically reshapes the mutational landscape of the metabolic enzyme dihydrofolate reductase (DHFR). Selection under conditions that resolve highly active mutants reveals that 23.3% of all single point mutations in DHFR are advantageous in the absence of Lon, but advantage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
72
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(80 citation statements)
references
References 61 publications
(79 reference statements)
3
72
0
Order By: Relevance
“…Secondly, DMS of native DHFR -under experimental conditions designed to resolve mutational effects near WT -revealed many beneficial (activating) mutations [27]. There are two explanations for the relative paucity of beneficial and neutral mutations in the present dataset.…”
Section: G)mentioning
confidence: 77%
See 4 more Smart Citations
“…Secondly, DMS of native DHFR -under experimental conditions designed to resolve mutational effects near WT -revealed many beneficial (activating) mutations [27]. There are two explanations for the relative paucity of beneficial and neutral mutations in the present dataset.…”
Section: G)mentioning
confidence: 77%
“…THF then serves as a one-carbon donor and acceptor in the synthesis of thymidine, purine nucleotides, serine, glycine, and methionine. Because of these critical metabolic functions, DHFR activity is strongly linked to growth rate, and under appropriate conditions, E. coli growth rate can be used as a proxy for DHFR activity [21, 27]. Prior work found that the modest in vitro allosteric effect of DL121 conferred a selectable growth rate advantage in vivo : when an E. coli DHFR deletion strain (ER2566 ΛfolAΔthyA ) was complemented with DL121, the resulting strain grew 17% faster in the light than in the dark [21].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations